Online psychoeducation in the COVID-19 pandemic situation: an effort to improve mental health - Edilburga Wulan Saptandari; Zafira Rahmania Nur Shabrina; Acintya Ratna Priwati (University of Merdeka Malang, 2022)
The pandemic situation that occurs often has a psychological impact on the people who experience it. This community service program aims to provide psychoeducation to the public regarding the psychological impacts that may be felt due to the COVID-19 situation. The program is carried out online in the form of UKP Bersinergi UKP Berbagi through WhatsApp, Live Instagram, and Zoom Meeting lectures. This program was held four times in April – October 2020. The keynote speakers in this program are psychologists, while the participants are educational personnel at UGM for Whatsapp lectures and public for Live Instagram and Zoom Meeting. Based on the evaluation given after the event, the UKP Bersinergi UKP Berbagi program is considered effective in providing psychoeducation for participants. This can be seen from the positive response submitted through the evaluation form. In addition, the results of a satisfaction survey related to the UKP Bersinergi UKP Berbagi program during the COVID-19 pandemic showed that most of the participants were satisfied with the services provided.